(untitled) (Web of Teachers: Inderscience Research, 2024)
The purpose of the study: to study the awareness of students about information and communication technologies in the field of medicine, to identify factors affecting the effectiveness of training for the implementation of telemedicine counseling. Material and methods: analysis and generalization of scientific, methodological and foreign literature, a test questionnaire for future general practitioners (graduates of the 6th year of the medical faculty of the Tashkent Medical Academy) and analysis of its results. The test was conducted on the basis of questions from the program of additional professional education of doctors in the specialties of “family medicine”. 32 undergraduate students of the 6th year of the Faculty of Medicine took part in the survey. Results. According to a survey of students of future family doctors (61%), special software, trained staff and stable communication are necessary for the effective implementation of telemedicine services in practice. An analysis of the use of information and digital technologies in the daily practice of the studied contingent showed that about 80% of the surveyed students of medical faculties regularly work in an Internet search engine, and 38% use email in their activities. However, for medical students, there is not enough understanding of telemedicine and orientation to its fields of application (42%). Conclusion. The introduction of telemedicine technologies into the educational process serves to prepare doctors for further effective work in hospitals and polyclinics and to provide high-quality medical care to patients.